Posttraumatic stress in school-age children and adolescents: medical providers’ role from diagnosis to optimal management - Ramsdell KD; Smith AJ; Hildenbr; AK; Marsac ML (Dove Medical Press, 2015)
Katharine Donlon Ramsdell,1 Andrew J Smith,1 Aimee K Hildenbrand,2 Meghan L Marsac3 1Department of Psychology, Virginia Tech, Blacksburg, VA, 2Department of Psychology, Drexel University, Philadelphia, PA, 3University of Pennsylvania and The Children’s Hospital of Philadelphia, Philadelphia, PA, USA Abstract: Millions of children and adolescents each year are exposed to potentially traumatic events (PTEs), placing them at risk for posttraumatic stress (PTS) disorder symptoms. Medical providers play an important role in the identification and treatment of PTS, as they are typically the initial point of contact for families in the wake of a PTE or during a PTE if it is medically related (eg, injury/illness). This paper offers a review of the literature focused on clinical characteristics of PTS, the assessment and diagnosis of PTS, and current effective treatments for PTS in school-age children and adolescents. The clinical presentation of PTS is often complex as symptoms may closely resemble other internalizing and externalizing disorders. A number of screening and evaluation tools are available for medical providers to assist them in the accurate diagnosis of PTS. Treatment options are available for youth at minimal risk of PTS as well as for those with more intensive needs. Additional training regarding trauma-informed medical care may benefit medical providers. By taking a trauma-informed approach, rooted in a solid understanding of the clinical presentation of PTS in children and adolescents, medical providers can ensure PTS does not go undetected, minimize the traumatic aspects of medical care, and better promote health and well-being. Keywords: posttraumatic stress, medical traumatic stress, children, primary care, assessment, treatment